Analisis Strategi Pemasaran Pada Produk UMKM Minuman Herbal “BIYENG” - Munawaroh, Siti; Redjeki, Sri; Prasetiyorini, Pudhak (LPPM Universitas PGRI Argopuro Jember, 2024)
Biyeng Herbal Drink is a brand of MSME product that is in great demand by the public and is already circulating in Banyuwangi Regency. Since the initial launch of the product until now, the marketing of Biyeng Herbal Drink has remained stable and production has increased among the people of Banyuwangi. The increase in production in one week reached 500 bottles, initially only producing 30-80 bottles per week. The marketing strategy used by Biyeng Herbal Drinks is able to face competition with similar products. The marketing of Biyeng Herbal Drink products is circulating amidst the popularity of contemporary drinks. The innovation created by the Biyeng Herbal Drink means that herbal drinks are no longer a drink that is put aside as a drink that is less popular with the public. This research focuses on analyzing the marketing strategy of Biyeng Herbal Drinks. The aim of the research is to determine the marketing strategy used in Biyeng Herbal Drinks. The research method uses descriptive-qualitative methods, with data collection techniques of observation, interviews and documentation. Data analysis techniques used include: data collection, data reduction, data display, and conclusion drawing/verification. The research results show that the Biyeng herbal drink segment is segmented based on demographics and product benefits. The target market is herbal drink connoisseurs and consumers who prioritize the benefits of products in the age range from teenagers to adults. Positioning lies in highlighting product characteristics, price and product quality. The marketing strategy used is the 4P marketing mix which consists of product, price, place and promotion. Even though there were several obstacles in the production and marketing process, Biyeng Herbal Drinks was able to find an alternative solution. Maintaining product quality, consistently informing about product procurement and maintaining relationships are ways to maintain consumer purchasing interest.